KH Hasyim Asy’ari On Seeking Knowledge And Teacher's Virtue - Ahmad Qomaruddin; Arina Zulva Maulida (Journal of Multidisciplinary Science, 2022)
An educational assessment is not only about report card scores or a good compulsive achievement index, more than that, education is also an effort to make a whole person. Many people today only look at the material and therefore neglect the true essence of education. This paper is here for a reference to the education system that has been pioneered by KH Hasyim Asy’ari who makes people educated is not only academic but also from the awareness of the heart. The research method carried out uses a qualitative approach to literature studies. The author collects data sources from various relevant references to conservative religious thought promoted by KH Hasyim Asy’ari. Data analysis techniques are carried out using the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The results of the study describe the educational thinking of KH Hasyim Asy’ari, Tebuireng Islamic boarding school, educational thought or philosophy of Islamic education of KH Hasyim Asy'ari include virtue science and science experts and virtue teaches and studies science, ethics for knowledge seekers, student ethics towards teachers, and teacher ethics towards students.